B2B planning and strategy - Bottom, John (Henry Stewart Talks, 2008)
Reducing the complexity of planning B2B campaigns, B2B compared to B2C, What makes B2B campaigns more complex for planners?, Product complexity, Complexity of target audience, Humanizing the decision making unit, Complexity of buying process, Stage by stage approach to the sales cycle, Activity planning: one step at a time
Archived at 2022/03/17